Fungicidal Properties of the Essential Oil of Hesperozygis marifolia on Aspergillus flavus Link - Marco Martín González-Chávez; Norma Cecilia Cárdenas-Ortega; Salud Pérez-Gutiérrez; Cristina Andrea Méndez-Ramos (Molecules, 2011)
The chemical composition of the essential oil from Hesperozygis marifolia was analyzed by gas chromatography-mass spectrometry (GC-MS), and fourteen compounds were identified. (R)-pulegone (40.75%), isomenthone (30.34%) and menthone (4.46%) were found to be the main components of the oil. The essential oil at a concentration of 2.0 mg/mL and (R)-pulegone at concentration of 0.8 mg/mL completely inhibited the growth of Aspergillus flavus Link. The fungicidal effects of this essential oil warrant further research into its potential for commercial use.